The challenges of the wind. Ecology of serious leisure in the Brazilian Northeast - Sirost, Olivier; Andrieu, Bernard; Dantas da Costa Sobral, Jullya Bheatriz; Da Nóbrega, Petrucia (Frontiers in Sports and Active Living, 2024)
The aim of this study is to understand the development of windsports and the challenges faced by wind-based leisure activities.The socio-historical dynamics behind the development of wind leisure are analysed on the basis of specialised tourism blogs, as well as a field study carried out in the Northeast Region of Brazil, combining ethnographic observations and semi-structured interviews with 6 wind leisure enthusiasts. All the data is processed using the serious leisure perspective tools developed by Stebbins, and the body ecology tools developed by Andrieu et al.The results show that wind sports provide a dual continuum. First of all, there are the practitioners, from Neophyte to Devotee Worker. Then there is the junction between land, water and air, where wind practices ensure a dual aesthetic. On the one hand, riders are united by a community of flow, emotion and sensation mediated by their relationship with the wind and the creation of play materials (waves, lagoons, trade winds). On the other hand, the tourist development of these practices serves a political narrative based on postcard aesthetics, enabling wind concessions to be traded for the development of wind farms.this original research calls for a more systematic exploration of wind practices and the hybridisation of natural elements, which seems to illustrate the crisis that modern sport and its institutions are going through today.